Clinical and Laboratory Characteristics and Follow Up Results of 121 Children with Juvenile Idiopathic Arthritis. Issue 3 (July 2013) - Ece, Aydın; Şen, Velat; Yel, Servet; Güneş, Ali; Uluca, Ünal; Tan, İlhan; Karabel, Duran; Yıldırım, Buğra; Şahin, Cahit
No abstract available